Biological incorporation of human acellular dermal matrix used in Achilles tendon repair - Bertasi, Giampietro (Cell Tissue Bank, 2017)
Human acellular dermal matrices (ADMs) are used successfully in a variety of procedures, including sports medicine related, wound repair, and breast reconstructions, but the mechanism of repair is still not fully understood. An opportunity to explore this mechanism presented itself when a patient experienced a rerupture of the native tendon due to a fall that occurred 2 months after undergoing an Achilles tendon repair using Matracell treated ADM. The ADM was removed and an extensive histology analysis was performed on the tissue. Additionally, a literature review was conducted to determine the mechanism of ADM integration into the tendon structure and explore if differences in this mechanism exist for different types of human ADMS. The histology analysis demonstrated that the healing process during a tendon reconstruction procedure is similar to that of wound healing. Furthermore, the literature review showed that differences exist in the mechanism for integration among various human ADMs and that these differences may be due to variances in the methods and technologies that manufactures use to process human ADMs.